Women, Dresses and Fashion in Wenceslao Ayguals de Izco's Universe (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2017)
This essay is an attempt of approach to the work of Ayguals de Izco and nineteenth-century society represented in his narrative through the analysis of prevailing customs and fashion in mid-nineteenth-century Spain. Our analysis is based on his famous trilogy (María o la hija de un jornalero, Marquesa de Bellaflor o el niño de la Inclusa, Palacio de los crímenes o El pueblo y sus opresores) and three other novels: Pobres y ricos o la bruja de Madrid, Los pobres de Madrid and La Justicia divina o El hijo del deshonor.Key words: Ayguals de Izco, fashion, customs, serial novel, Spanish society.